INOVASI DALAM PRODUKSI DAN PEMASARAN KERAJINAN DARI MATERIAL DAUR ULANG - Putra, Alfa Santoso Budiwidjojo (Universitas Mataram, 2024)
The Bunga Raya Waste Bank introduced an innovative program to address waste management challenges through the production and marketing of recycled products. This program's primary goals are to enhance environmental awareness, decrease trash volume, and boost neighborhood economic income. The program included skills training, production facilities, collaboration with local artisans, offline marketing strategies, and building a local brand. As a result, the program increased individual incomes, reduced waste entering landfills, and increased community involvement in environmental conservation. Challenges faced included limited capital, fluctuating market demand, and lack of public awareness. However, the program demonstrated great potential in promoting sustainable local economic development while addressing environmental challenges.